Perlindungan Hak Pasien Atas Kerahasiaan Data Pribadi Dalam Pelaksanaan Rekam Medis Elektronik Di Unit Rawat Jalan Rsu Budi Rahayu Pekalongan - Elvika Chandra Pranata; B. Resti Nurhayati; Hartanto Hartanto (Universitas Katolik Soegijapranata Semarang, 2025)
Abstract: The right to privacy of personal health data and information is individual’s right. The advancement of digital technology encourages medical records to be managed electronically with principles of data and information security and confidentiality. Electronic Medical Records (EMR) are at risk of leakage, which can harm both patients and hospitals. Therefore, it is necessary to review how patients’ rights to the confidentiality of personal data are protected in the implementation of EMR. The research approach used is the juridical-sociological method. The research specification is analytical-descriptive with qualitative data analysis. From the research, it is concluded that there are regulations at Budi Rahayu Hospital that govern the protection of patients’ rights to the confidentiality of personal data in the implementation of EMR. The implementation of protecting patients' rights to the confidentiality of personal data in Electronic Medical Records (RME) at the Outpatient Department of RSU Budi Rahayu is done by providing access restrictions for each account according to its purpose, user ID and password for each account are confidential, reporting only as needed and according to regulations. Access to medical record contents is granted solely to patients or their closest family members with patient consent, healthcare financiers as permitted, and entities specified by legal regulations. Access to EMR is restricted to local server IP addresses and not publicly disclosed, with a firewall used to secure the SIMRS’ system. Up until the time of the research, there had been no leakage of patients’ data in EMR. Challenges in implementing the protection of patients’ rights to confidentiality of personal data in EMR include: some employees not changing their account passwords, the presence of autofill features, lack of ability to operate EMR, lack of clarity on vendor access restrictions to EMR, lack of patients’ knowledge regarding the confidentiality of their personal data, and incomplete interoperability capabilities of EMR.Abstrak: Hak atas kerahasiaan data dan informasi kesehatan pribadi merupakan hak yang dimiliki oleh setiap orang. Perkembangan teknologi digital mendorong rekam medis diselenggarakan secara elektronik dengan prinsip keamanan dan kerahasiaan data dan informasi. Rekam Medis Elektronik (RME) berisiko mengalami kebocoran sehingga merugikan pasien maupun rumah sakit. Oleh karena itu, perlu ditinjau bagaimana perlindungan hak pasien atas kerahasiaan data pribadi dalam pelaksanaan RME. Metode pendekatan menggunakan metode yuridis sosiologis. Spesifikasi penelitian adalah deskriptif analitis dengan analisis data kualitatif. Dari hasil penelitian disimpulkan bahwa terdapat peraturan di RSU Budi Rahayu yang mengatur tentang perlindungan hak pasien atas kerahasiaan data pribadi dalam pelaksanaan RME. Pelaksanaan perlindungan hak pasien atas kerahasiaan data pribadi dalam RME di URJ RSU Budi Rahayu dilakukan dengan cara memberikan batasan hak akses, user ID dan password setiap akun rahasia, serta melaporkan informasi hanya sesuai kebutuhan dan ketentuan. Akses ke isi rekam medis hanya diberikan kepada pasien atau keluarga terdekat yang memiliki izin dari pasien, penjamin pembiayaan pasien sesuai dengan izin yang diberikan, serta pihak yang ditetapkan oleh peraturan perundang-undangan. Akses ke RME hanya dapat dilakukan melalui IP address server lokal yang tidak dipublikasikan, dengan penggunaan firewall untuk mengamankan sistem SIMRS. Sampai dengan saat penelitian dilakukan, belum pernah terjadi kebocoran data RME pasien. Hambatan pelaksanaan perlindungan hak pasien atas kerahasiaan data pribadi dalam RME di URJ RSU Budi Rahayu yaitu: kata sandi belum dirubah, adanya fitur autofill, kurangnya kemampuan mengoperasikan RME, kurangnya kejelasan batasan hak akses vendor, kurangnya pengetahuan pasien tentang hak kerahasiaan data pribadinya, serta pelaksanaan RME belum sepenuhnya memiliki kemampuan interoperabilitas.